Association between Elevated TGA-IgA Titers and Older Age at Diagnosis with Absence of HBV Seroconversion in Celiac Children - Trovato, Chiara Maria (Vaccines (Basel), 2021)
Patients with celiac disease can have a low rate of protective hepatitis B (HBV) antibody titers after vaccination. We aimed to evaluate the HBV seroconversion in celiac disease (CD) children at the time of diagnosis as well as to identify the presence of possible predictive factors. Celiac disease children were prospectively enrolled and tested for antibodies against the S protein of HBV (HBsAg) at time of diagnosis between January 2009 and February 2020. Based on the serologic response to the vaccine, “responders” and “non-responders” were identified. Statistical analysis has been performed through R statistical software (3.5.1 version, R core Team) Of 96 CD children evaluated, 41.7% (n = 40) showed non-protective or absent antibody titers against HBV. Elevated IgA-antibodies against transglutaminase 2 (TGA-IgA) values and older age at diagnosis were associated with an absent seroconversion to HBV vaccine, while presenting symptoms were not significant. An elevated prevalence of absent seroconversion to HBV vaccine exists in this cohort of CD patients at the time of disease diagnosis. Elevated TGA-IgA titers and older age at diagnosis seem to negatively predict seroconversion. Further studies are needed to identify the real profile of “non-responders”, aiming to organize surveillance and eventual revaccination strategy.